Russian "émigré" culture: conservatism or evolution? - Flamm, Christoph; Keazor, Henry; Marti, Roland (Cambridge Scholars Publishing, 2013)
A quarter of a century ago, glasnost opened the door for a new look at Russian émigré culture unimpeded by the sterile concepts of Cold War cultural politics. Easier access to archives and a comprehensive approach to culture as a multi-faceted phenomenon, not restricted to single phenomena or individuals, have since contributed to a better understanding of the processes within the émigré community, of its links with the lost home country, and of the interaction with the cultural life of the c...